1998
DOI: 10.1038/sj.ijo.0800549
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of weight change in men: Results from The Health Professionals Follow-Up Study

Abstract: OBJECTIVE: Since the prevalence of adult obesity is increasing in the United States, we examined the effect of changing common habits (exercise, TV viewing, smoking and eating habits) on four year change in body weight. DESIGN: A prospective cohort study of US male health professionals with follow-up from 1988±1992. Participants were 19 478 men aged 40±75 in 1986, who were free of cancer, coronary heart disease, stroke and diabetes. METHODS: Multiple regression was used to determine the association between fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 32 publications
5
117
2
2
Order By: Relevance
“…In recent decades the urbanisation process in Western societies has been associated with lower energy output at work, in household tasks, increased use of public transportation, cars and lifts, among other factors (Haapanen et al, 1997;Coakley et al, 1998). An increased BMI has been reported among ex-smokers (Flegal et al, 1995;Molarius et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades the urbanisation process in Western societies has been associated with lower energy output at work, in household tasks, increased use of public transportation, cars and lifts, among other factors (Haapanen et al, 1997;Coakley et al, 1998). An increased BMI has been reported among ex-smokers (Flegal et al, 1995;Molarius et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of large cohort studies that have tracked weight change in the United States (Coakley et al, 1998;Fine et al, 1999;Field et al, 2001a) and elsewhere (Heitmann and Garby, 1999;Hughes et al, 2002). However, longitudinal studies in which increases in weight and body mass index (BMI) are examined in relation to socio-demographic variables in a population cohort in the United Kingdom are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In the decade that followed, however, more than a dozen prospective studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , conducted over periods ranging from 1 to 15 years, have suggested that dieting to lose weight is associated with future weight gain and obesity, with many of them showing this association even after adjustment for potential confounders such as baseline BMI, age and several lifestyle and behavioural characteristics. Particularly informative are the 3-year follow-up studies of Stice et al (15) showing that adolescents with baseline dieting had three times the risk of onset of obesity than the non-dieters, and the 6-15-year follow-up study of Korkelia et al (16) reporting that initially normal-weight subjects who were attempting to lose weight had two times the risk of major weight gain (> 10 kg) than non-dieters.…”
Section: Prospective Studies Linking Dieting To Future Weight Gainmentioning
confidence: 99%